The Effect of Remifentanil on Succinylcholine Induced Changes in Serum Potassium and Creatine Kinase: A Prospective Randomized Double blind Study - Nasseri, Karim; Shami, Shoaleh; Shirmohammadi, Mousa; Sarshivi, Farzad; Ghadami, Negin (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Succinylcholine is still included as drugs favored by anesthetists because of its rapid onset and short duration of action. However, it can bring about complications such as hyperkalemia and increased serum creatine phosphokinase (CPK). This study aims at evaluating the effects of remifentanil on succinylcholine-induced postoperative changes in serum potassium and CPK. Methods: In this study, 59 patients with short term lower abdominal surgery were randomly divided into two groups. In the first group (control group), 2 ml normal saline was used before injecting anesthetic drugs while in the second group (study group), 1 mcg/kg of remifentanil was injected. The patients were anesthetized with a combination of fentanyl (1 mg/kg) and propofol (2 mg/kg). Besides, succinylcholine (1.5 mg/kg) was used for muscle relaxation and tracheal intubation. Serum potassium (before and 5 min after tracheal intubation), CPK (before anesthetic injection and 24 h after surgery) and hemodynamic parameters (including systolic, diastolic and mean arterial blood pressure and heart rate) were recorded. Results: Serum levels of potassium and CPK before and after induction of anesthesia showed no significant difference in both groups. Systolic, diastolic, and mean arterial blood pressure and heart rate in both groups after induction significantly changed. Compared to saline, remifentanil significantly stabilized hemodynamic changes after intubation. Conclusions: The results suggest that remifentanil has no prophylactic effect on succinylcholine-induced CPK and potassium levels. However, it improves stability of hemodynamic variables.